2019
DOI: 10.1002/jor.24158
|View full text |Cite
|
Sign up to set email alerts
|

Targeted proteomics of hip articular cartilage in OA and fracture patients

Abstract: Osteoarthritis (OA) is a common chronic disease, causing joint pain and reduced physical function. OA progresses slowly over a period of several years; to avoid an exacerbation of symptoms, it is critical to able to diagnose the disease as early as possible. The identification of disease‐specific biomarkers may enable such an early diagnosis. The aim of this study was to investigate potential biomarkers of cartilage metabolism in OA using a targeted multiplex approach by single reaction monitoring. Intact look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…In humans, chondrodysplasia-causing mutations in COMP, collagen IX, or MATN3 are frequently associated with premature osteoarthritis. Matrilin-3 is present at low levels in the joint articular surface and its deposition is upregulated in cartilage and in the synovial fluid of patients with OA as a consequence of cartilage degradation [56][57][58][59][60]. Studies with recombinant MATN3 and human primary chondrocytes have revealed that MATN3 exhibits a context-dependent anabolic or catabolic function by influencing the expression of pro-inflammatory cytokines, ECM degradation enzymes, and ECM synthesis [59,[61][62][63] through the modulation of protein kinase B (AKT) [59], interleukin-6 [62], and interleukin-1 [63,64] signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, chondrodysplasia-causing mutations in COMP, collagen IX, or MATN3 are frequently associated with premature osteoarthritis. Matrilin-3 is present at low levels in the joint articular surface and its deposition is upregulated in cartilage and in the synovial fluid of patients with OA as a consequence of cartilage degradation [56][57][58][59][60]. Studies with recombinant MATN3 and human primary chondrocytes have revealed that MATN3 exhibits a context-dependent anabolic or catabolic function by influencing the expression of pro-inflammatory cytokines, ECM degradation enzymes, and ECM synthesis [59,[61][62][63] through the modulation of protein kinase B (AKT) [59], interleukin-6 [62], and interleukin-1 [63,64] signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of IL-17 in synovial fluid may also discriminate an OA subtype with faster cartilage loss, reduced osteophytes, and increased adipokines. Increased pain in hip OA patients is associated with increased IL-6, visfatin, and leptin, while in knee OA patients, increased leptin, reduced adiponectin and reduced adiponectin–leptin ratio are associated with pain [ 89 91 ]. Given the association of OA with metabolic disease, it is feasible that lipid and metabolomic markers may define specific OA subtypes and impact disease progression as they do in cancer [ 92 94 ].…”
Section: Disease Stratification—breaking Down a Spectrum Of Diseases mentioning
confidence: 99%
“…Kjelgaard-Petersen et al (2018) have previously shown that full-depth bovine articular cartilage explants (BEX) treated with oncostatin M in combination with TNFα (O + T) were a reliable translational model for rheumatoid arthritis by successfully back-translating the serological biomarker results from a phase III clinical study (OSKIRA-1) [32]. Proteomic technologies allow for a large-scale unbiased investigation, making it possible to identify factors involved in joint disease progression and build a library of mediators: previous studies have revealed numerous cytokines, proteases, and matrix fragments in serum, synovial fluid, and articular cartilage of OA patients [33][34][35][36]. Therefore, adapting the BEX model for studying IL-17-mediated articular cartilage changes and combining it with proteomics could contribute to a better understanding of molecular events involved in IL-17-mediated cartilage turnover and identification of its biomarkers.…”
Section: Introductionmentioning
confidence: 99%